Morphological description and DNA barcoding study of Paramignya trimera collected in Khanh Hoa, Vietnam - Cam Mien, Phi Thi; Bich Ngoc, Pham; Hoang Ha, Chu; Duc Bach, Nguyen (Vietnam Journal of Biotechnology, 2021)
Paramignya trimera is a valuable traditional medicinal plant, typically distributing in Khanh Hoa, Vietnam. In recent years, P. trimera has been exploited to treat liver diseases such as hepatitis, cirrhosis and liver cancers. The recorded during the investigation, in Khanh Hoa currently appears a number of species with similar phenotypes known collectively as P. trimera and appeared some morphology with differences in leaf morphology and thorns. Therefore, this study was carried out for identification, breeding and propagation conservation.This study has been described, characterized morphological characteristics and analyzed DNA barcodes based on ITS, matK and rbcL gene markers. About the morphology, P. trimera is distinguished from other species of the genus Paramignya with the following characteristics: elongated, single leaf, leaf-shaped lobe end, leaf veins shaped like a feather. Petiole with big, pointed and straight spines. Corolla 3, 6 stamens, upper election, with three sepals and two ovule leaves, the seed has a  seed coat. The analysis of DNA barcodes shows that the results combination of the analysis of the three regions of ITS, matK and rbcL can be used to determine the genetic relationship between five samples of P. trimera. The nucleotide sequence lengths of the samples for the three regions of the ITS, matK and rbcL genes are 850 bp, 850 bp and 500 bp, respectively. On the basis of phenotypic tree analysis, the samples (X1, X2, X3, X4, X5) have the same evolutionary origin in ITS, matK and rbcL. Base on to identified the five morphological forms of P. trimera distributed in Khanh Hoa as the same species and expanded the distribution area as well as in-depth research on P. trimera morphologies in Khanh Hoa, Vietnam.